Formulation and characterization of sertu kaolin clay paste for cleaning of medical equipment and wound treatment - Ahmad, Zuraida; Samat, Noorasikin; Sarifuddin, Norshahida; Awang, Mohd Shukrimi; Che Ahmad, Aminudin; Al-Azmi, Abdul Rahman; Yusuff, Mohamad Ikhwan; Radzi, Nursyazwana (Penerbit UTM Press, 2025)
The treatment of the wounds inflicted by dogs and wild boars becoming a significant public concern. From Islamic contexts, it demands effective and Shariah-compliant cleaning methods. Current practices predominantly employ soil-based soap, raising questions about its scientific efficacy and safety for wound treatment and medical equipment cleansing. This study is executed to formulate and characterize a Shariah-compliant kaolin clay paste designed for sertu applications in the medical field, for both wound areas and medical equipment cleansing. Kaolin clay was selected as the soil medium in the formulated sertu clay paste and underwent various characterizations, including X-ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR) analyses. XRD analysis confirmed the presence of kaolinite in the kaolin clay. This is also further evidenced by the presence of bonds between Al and Mg ions and hydroxyl groups in the FTIR spectra. The irregular morphology of the kaolin particles observed through SEM, contributed to an increase in surface area, thereby enhancing the interaction between clay and other components. The formulated clay paste was further evaluated through pH measurement, irritation analysis, antimicrobial testing, and corrosion testing to assess its performance. The results indicated that the formulation produced a stable sertu clay paste, with pH values ranging from 8.34 to 9.52 and a primary irritation index (PII) of 4.38 which is within acceptable range for wound treatment. Additionally, the paste proved suitable for cleansing medical instruments, as no significant corrosion or bacterial growth was observed